Some factors affecting soybean viability and emergence in the lowland tropics - Nangju, D.; Wien, H.C.; Singh, T.P. (1975)
Seed viability and emergence is one of the most important problems affecting soybean production in West Africa. Results from the multi-location yield trials indicated that introduced cultivars such as Bossier, Jupiter and Improved Pelican showed excellent adaptation and high yields provided seedling emergence was high and plant population was optimum. Diseases and insects are as yet not a major problem. An integrated approach on soybean emergence problem has been carried out by the IITA physiologist, agronomist and soybean breeder to identify factors affecting soybean viability and emergence, and to find a practical solution for this problem. Results obtained so far indicated that poor germination was observed in some cultivars right from the time they were harvested. After harvest, factors such as seed quality, method of threshing, temperature during drying, length and method of storage could also lower the viability of soybean seeds; their effects were more pronounced in some cultivars than in others. At planting, sowing depth I soil temperature and soil moisture were found to influence seedling emergence. Soil temperature up to 42 C during rainy season at Ibadan, Nigeria has been recorded, and 2 hours of 42C soil temperature was found to reduce hypocotyl extension by more than 70% in soybean. Seed dressing with a fungicide, sowing depth between 2.5 - 5 cm, adequate soil moisture at planting and mulching are all beneficial in improving seedling emergence. The present efforts are being concentrated on developing suitable screening methods for high seed quality and Viability, and ability to tolerate high soil temperatures during emergence.